Cellular MRI Contrast via Coexpression of Transferrin Receptor and Ferritin - Deans, Abby E. (2006)
Recently there has been growing interest in the development and use of iron-based contrast agents for cellular imaging with MRI. In this study we investigated coexpression of the transferrin receptor and ferritin genes to induce cellular contrast in a biological system. Expression of transgenic human transferrin receptor and human ferritin H-subunit was induced in a stably transfected mouse neural stem cell line. When grown in iron-rich medium, the transgenic cells accumulated significantly more iron than control cells, with a trend toward an increase in reactive oxygen species, but no detrimental effects on cell viability. This cellular iron significantly increased the transverse relaxivities, R(2) and [Formula: see text] , at 1.5 T and 7 T. By comparing measurements in the same cell samples at 1.5 T and 7 T, we confirmed the expected increase in relaxivity with increasing field strength. Finally, supplemented transgenic cells transplanted into mouse brain demonstrated increased contrast with surrounding neural tissue on [Formula: see text]-weighted MR brain images compared to controls. These results indicate that dual expression of proteins at different critical points in the iron metabolism pathway may improve cellular contrast without compromising cell viability.